Macrophage Migration Inhibitory Factor (MIF) Drives Murine Psoriasiform Dermatitis - Bezdek, Siegfried; Leng, Lin; Busch, Hauke; Mousavi, Sadegh; Rades, Dirk; Dahlke, Markus; Zillikens, Detlef; Bucala, Richard; Sadik, Christian D. (Frontiers in Immunology, 2018)
The immunomodulator Macrophage Migration Inhibitory Factor (MIF) exerts pleiotropic immunomodulatory activities and has been implicated in the pathogenesis of diverse inflammatory diseases. Expression levels of MIF are also significantly elevated in the skin and serum of psoriasis patients, but the pathogenic significance of MIF in psoriasis is unknown. We have therefore addressed the role of MIF in two mouse models of psoriasis, namely in the imiquimod-induced psoriasiform dermatitis (IIPD) and the IL-23-induced dermatitis model. Daily treatment with Aldara™ cream, containing imiquimod, markedly increased the abundance of MIF in the skin and generated a cellular skin expression pattern of MIF closely resembling that in human plaque psoriasis. Deficiency in MIF significantly alleviated IIPD. On the clinical level, all hallmarks of psoriasiform dermatitis, including erythema, skin infiltration, and desquamation were reduced in Mif-/- mice. On the histopathological level, MIF deficiency decreased keratinocyte hyperproliferation, inflammatory cell infiltration, specifically with respect to monocyte-derived cells, and dermal angiogenesis, suggesting that MIF may be involved in the pathogenesis of psoriasiform dermatitis through several mechanisms. Similarly, MIF deficiency also significantly reduced disease in the IL-23-induced dermatitis model, suggesting that MIF is involved in the pathogenic pathways activated by IL-23 and required to achieve full-blown psoriasiform dermatitis. Collectively, our results lend support to a possible disease-promoting role of MIF in psoriasis, which should be further investigated.